Pengaruh Budaya Organisasi “Sikap Dasar KLIK-Jujur” Terhadap Kinerja Pegawai - Gugi Gustaman; Laila Refiana Said (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2020)
This research aims to determinate and analyze the influence of organizational culture “Basic Attitudes KLIK-Honest” (exogenous) as an independent variable on employee performance (endogenous) as the dependent variable in the Office of Supervision and Service of Customs and Excise Type B Banjarmasin. This research method use a questionnaire with 105 employees in the Office of Supervision and Service of Customs and Excise Type B Banjarmasin as respondents. The Measurement of variables used a Likert Scale with a weight scale from 1 to 5. To determine the effect of exogenous variables on endogenous variables, this study used Structural Equation Modelling (SEM) analysis using AMOS 22.00. The results of the study concluded that there was a positive and significant influence of exogenous variables on endogenous variable, that the Organizational Culture of “Basic Attitudes KLIK-Honest” had a positive and significant effect on Employee Performance in the Office of Supervision and Service of Customs and Excise Type B Banjarmasin